2015
DOI: 10.1063/1.4907661
|View full text |Cite
|
Sign up to set email alerts
|

On the physical processes ruling an atmospheric pressure air glow discharge operating in an intermediate current regime

Abstract: Low-frequency (100 Hz), intermediate-current (50 to 200 mA) glow discharges were experimentally investigated in atmospheric pressure air between blunt copper electrodes. Voltage-current characteristics and images of the discharge for different inter-electrode distances are reported. A cathode-fall voltage close to 360 V and a current density at the cathode surface of about 11 A/cm 2 , both independent of the discharge current, were found. The visible emissive structure of the discharge resembles to that of a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 29 publications
4
21
1
Order By: Relevance
“…The discharge current density varied in the range 1-5 A/cm 2 , whereas the reduced electric field was about 30-40 Td. These values are in according to those reported for atmospheric pressure glowlike discharges in molecular gases [20,26]. For E/N larger than about 40 Td (corresponding to E [ 0.8 9 10 5 V/m), no stationary solution was found; thus indicating that the arc reattachment is essentiality a threshold process.…”
Section: Resultssupporting
confidence: 78%
“…The discharge current density varied in the range 1-5 A/cm 2 , whereas the reduced electric field was about 30-40 Td. These values are in according to those reported for atmospheric pressure glowlike discharges in molecular gases [20,26]. For E/N larger than about 40 Td (corresponding to E [ 0.8 9 10 5 V/m), no stationary solution was found; thus indicating that the arc reattachment is essentiality a threshold process.…”
Section: Resultssupporting
confidence: 78%
“…Several kinetic schemes have been proposed in the literature for modelling atmospheric pressure nonequilibrium air discharges, such as streamers [1,2], low-current arc and glow discharges at rest (or in low gas flows) [3][4][5][6], glow discharges in fast gas flows [7][8][9], and high-current pulsed discharges [10][11][12][13][14][15]. It is found that the ionization by electron impact of O 2 and N 2 molecules dominates at low-gas temperature (T g is below the range of 1000-2000 K [10,14,15]), while the electron-impact ionization of NO molecules is written as: e + NO → NO + + e, (R3) (1) where R refers to the reactions used in the model.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the ionization by electron impact of O 2 and N 2 molecules dominates at low-gas temperature (T g is below the range of 1000-2000 K [10,14,15]), while the electron-impact ionization of NO molecules is written as: e + NO → NO + + e, (R3) (1) where R refers to the reactions used in the model. This electron-impact ionization is favored by its low ionization energy of 9.27 eV and dominates at high gas temperatures [3,4,14,15]. At T g > 4500 K, the associative ionization in ground-state atomic collisions can be shown as:…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations